Inside Back Cover: Electrolytes Ageing in Lithium‐ion Batteries: A Mechanistic Study from Picosecond to Long Timescales (ChemSusChem 21/2015). Issue 21 (2nd November 2015) - Ortiz, Daniel; Jiménez Gordon, Isabel; Baltaze, Jean‐Pierre; Hernandez‐Alba, Oscar; Legand, Solène; Dauvois, Vincent; Si Larbi, Gregory; Schmidhammer, Uli; Marignier, Jean‐Louis; Martin, Jean‐Frédéric; Belloni, Jacqueline; Mostafavi, Mehran; et al.
Abstract : Ageing of electrolytes used in batteries is a major issue for researchers and industry, as it represents an important cost in the development of new batteries. Past failures to adequately characterize the degradation processes of the electrolyte have led to potentially disastrous safety issues. It is, therefore, paramount to have an in‐depth understanding of the underlying ageing phenomena. On the Inside Back Cover picture, we show that radiolysis techniques can induce similar mechanisms in the electrolyte, allowing for an accelerated assessment of the ageing phenomena within hours. More details can be found in the Full paper by Ortiz et al. onpage 3605 in Issue 21, 2015 (DOI:10.1002/cssc.201500641 ).